Comparison Analysis of Bank Muamalat Indonesia's Financial Performance Using the Income Statement Approach and Value Added Approach - Khairun Nisa; Nur Laila; Rahmat Daim Harahap (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This study aims to compare the financial performance of PT Bank Muamalat Indonesia based on the Income Statement Approach and Value Added Approach in terms of financial ratios consisting of ROA, ROE, and NPM. This research is a qualitative descriptive study using secondary data. The data used are financial reports published by PT Bank Muamalat Indonesia Tbk from 2017-2021. The subject of this research is the financial statements of PT Bank Muamalat Indonesia. The object used in this study is the financial performance of Islamic banks. The results showed that by using the ROA, ROE, and NPM ratios there were significant differences, in this study the Value Added Approach approach of banks was able to produce better financial performance compared to the Income Statement Approach, due to the average value of the ratios of ROA, ROE and The NPM in the Value Added Approach is relatively higher than the Income Statement Approach. The average value of the ROA ratio in the Value Added Approach is 6.23% while in the Income Statement Approach it is 0.055%. The average value of the ROE ratio in the Value Added Approach is 81.57% while in the Income Statement Approach it is 0.50%. The average value of the NPM ratio in the Value Added Approach is 102.06%, while in the Income Statement Approach it is 0.60%. This shows that with the Value Added Approach approach, banks are able to generate better profits compared to the Income Statement Approach.